Neurovascular Coupling Is Impaired in Hypertensive and Diabetic Subjects Without Symptomatic Cerebrovascular Disease - Monteiro, Ana; Castro, Pedro; Pereira, Gilberto; Ferreira, Carmen; Sorond, Farzaneh; Milstead, Andrew; Higgins, James P.; Polónia, Jorge; Azevedo, Elsa (Frontiers in Aging Neuroscience, 2021)
The mechanistic link between hypertension, diabetes and cerebral small vessel disease (CSVD) is still poorly understood. We hypothesized that hypertension and diabetes could impair cerebrovascular regulation prior to irreversibly established cerebrovascular disease. In this study, 52 hypertensive patients [54% males; age 64±11 years; 58% with comorbid diabetes mellitus (DM)] without symptomatic cerebrovascular disease underwent transcranial Doppler (TCD) monitoring in the middle (MCA) and posterior (PCA) cerebral arteries, to assess vasoreactivity to carbon dioxide (VRCO2) and neurovascular coupling (NVC). 1.5T magnetic resonance imaging was also performed and white matter hyperintensity volume was automatically segmented from FLAIR sequences. TCD data from 17 healthy controls were obtained for comparison (47% males; age 60±16 years). Hypertensive patients showed significant impairment of NVC in the PCA, with reduced increment in cerebral blood flow velocity during visual stimulation (22.4±9.2 vs 31.6±5.7, p<0.001), as well as disturbed NVC time-varying properties, with slower response (lower rate time: 0.00±0.02 vs 0.03±6.81, p=0.001), and reduced system oscillation (reduced natural frequency: 0.18±0.08 vs 0.22±0.06, p<0.001), when compared to controls. VRCO2 remained relatively preserved in MCA and PCA. These results were worse in hypertensive diabetic patients, with lower natural frequency (p=0.043) than non-diabetic patients. White matter disease burden did not predict worse NVC. These findings suggest that hypertensive diabetic patients may have a precocious impairment of NVC, already occurring without symptomatic CSVD. NVC assessment could be useful as an early, non-invasive, surrogate marker for CSVD to guide therapies aimed to prevent clinically relevant cerebrovascular disease.